Flüchtlingsmonitoring : Endbericht - Brenzel, Hanna [Verfasser]; Brücker, Herbert [Verfasser]; Fendel, Tanja [Verfasser]; Guichard, Lucas [Verfasser]; Jaschke, Philipp [Verfasser]; Keita, Sekou [Verfasser]; Kosyakova, Yuliya [Verfasser]; Olbrich, Lukas [Verfasser]; Trübswetter, Parvati [Verfasser]; Vallizadeh, Ehsan (My University, 2019)
"Im Zuge der Flüchtlingszuwanderung seit 2015 und damals weitgehend fehlender Kenntnisse über Qualifizierung, Bildungsstatus und den Verlauf von Integrationsprozessen bei den Geflüchteten hat das BMAS im Oktober 2015 das Institut für Arbeitsmarkt- und Berufsforschung (IAB) mit einem Flüchtlingsmonitoring beauftragt. Dieses sollte die neu konzipierte IAB-SOEP-BAMF-Geflüchtetenbefragung auswerten und anhand deskriptiver und multivariater Analysen Hinweise für eine zielgerichtete Integrationspolitik liefern. Der Endbericht des IAB liegt dem BMAS nun hiermit vor." (Autorenreferat; BIBB-Doku)

"The high influx of refugees to Germany in recent years has confronted politicians and society with the challenge of promoting effective integration policies with limited information about the persons concerned. The aim of the present study is to provide scientific evidence to contribute to the debate and decision-making. Therefore, we use the IAB-BAMF-SOEP Survey of Refugees - a representative survey of refugees in Germany, surveyed in 2016 and 2017, which is elaborated in chapter 1. Chapter 2 describes the variation in the escape routes used by refugees as well as various hurdles (such as time and monetary costs) that refugees encountered on their escape to Germany. Chapter 3 highlights the differences and commonalities of personality traits between refugees, natives and other immigrants. Chapter 4 provides an overview on the skills, competencies and labor market experiences that refugees acquired before their migration to Germany and on the possibilities to recognize foreign educational degrees. Chapter 5 examines the progress in language acquisition and determinants of German language proficiency among refugees. Chapter 6 discusses refugees' values and attitudes, social contacts and experiences of discrimination. The final Chapter figures out the development and determinants of labor market integration of refugees in Germany." (authors' abstract; BIBB-Doku)
Keywords: P 1.5 Migranten; G 1.2.3 Qualifikationsentwicklungen; Flüchtling; Herkunftsland; Persönlichkeitsmerkmal; Berufliche Qualifikation; Berufserfahrung; Berufliche Integration; Deutsch als Fremdsprache; Werte